Sintesis dan Uji Antioksidan Senyawa 1,5-bis(3’-etoksi-4’-hidroksifenil)-1,4-pentadien-3-on (EHP) - ESTI MUMPUNI; ENJANG RUSNAWAN; EVI SULASTRI; INDRIANA PERMATASARI (Fakultas Farmasi Universitas Pancasila, 2010)
Synthesis of 1,5-bis(3’-etoxy-4’-hydroxyphenyI)-1,4-pentadiene-3-on (EHP) by aldol condensation method from ethyl Vanilin and acetone, using hydrochloride acid as a catalyst, has been conducted. Identification of the EHP compound was done through interpretation of UV-Vis, FT-IR, GC-MS and NMR data, The antioxidant activity of EHP (IC50 8.66 µg/mL) is higher than curcumin (IC50 11.44 µg/mL) as demonstrated by the DPPH method.